Investigating the impact of long term exposure to chemical agents on the chromosomal radiosensitivity using human lymphoblastoid GM1899A cells - Otilia Nuta (Nature Portfolio, 2021)
Abstract This study aimed to investigate the impact of chronic low-level exposure to chemical carcinogens with different modes of action on the cellular response to ionising radiation. Human lymphoblastoid GM1899A cells were cultured in the presence of 4-nitroquinoline N-oxide (4NQO), N-nitroso-N-methylurea (MNU) and hydrogen peroxide (H2O2) for up to 6 months at the highest non-(geno)toxic concentration identified in pilot experiments. Acute challenge doses of 1 Gy X-rays were given and chromosome damage (dicentrics, acentric fragments, micronuclei, chromatid gaps/breaks) was scored. Chronic exposure to 20 ng/ml 4NQO, 0.25 μg/ml MNU or 10 μM H2O2 hardly induced dicentrics and did not significantly alter the yield of X-ray-induced dicentrics. Significant levels of acentric fragments were induced by all chemicals, which did not change during long-term exposure. Fragment data in combined treatment samples compared to single treatments were consistent with an additive effect of chemical and radiation exposure. Low level exposure to 4NQO induced micronuclei, the yields of which did not change throughout the 6 month exposure period. As for fragments, micronuclei yields for combined treatments were consistent with an additive effect of chemical and radiation. These results suggest that cellular radiation responses are not affected by long-term low-level chemical exposure.